1975
DOI: 10.1016/s0022-5347(17)67149-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trimethoprim-Sulfamethoxazole on the Renal Excretion of Creatinine in Man

Abstract: Treatment with the chemotherapeutic combination of 160 mg. trimethoprim plus 800 mg. sulfamethoxazole twice daily increased the serum creatinine level by an average of 2 mg. per 1. in 21 patients. The effect was clearly reversible. The chemical analysis of creatinine was not affected by the addition of trimethoprim, sulfamethoxazole or their metabolites. In 2 subjects given the drug combination for 12 days renal excretion and 24-hour clearances of creatinine decreased but iothalamate 131I clearance was unchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
2

Year Published

1981
1981
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(85 citation statements)
references
References 12 publications
3
80
0
2
Order By: Relevance
“…In 1975, Berglund et al [29] found that therapy with 160 mg trimethoprim and 800 mg sulphamethoxazole b.i.d. in 21 patients reversibly increased plasma creatinine by an average of 2 mg L 21 (18 mmol L 21 ) without influencing GFR, measured by the clearance of I-iothalamate.…”
Section: Trimethoprimmentioning
confidence: 99%
“…In 1975, Berglund et al [29] found that therapy with 160 mg trimethoprim and 800 mg sulphamethoxazole b.i.d. in 21 patients reversibly increased plasma creatinine by an average of 2 mg L 21 (18 mmol L 21 ) without influencing GFR, measured by the clearance of I-iothalamate.…”
Section: Trimethoprimmentioning
confidence: 99%
“…In kidney transplant patients, many other factors may affect creatinine metabolism. For example, corticosteroids may alter the muscle massto-total body weight ratio (3), and the use of drugs, such as trimethoprim, may affect creatinine secretion in the proximal tubule (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…All equations will misinterpret a patient with ketoacidosis 41 or IgM myeloma 42 as su¡ering a loss in GFR and another with hyperbilirubinaemia 43 as demonstrating an improvement in function where there is in reality no such loss or improvement, but rather re£ects an analytical error in the measurement of serum creatinine. Administration of medications such as trimethoprim, 44 cimetidine 45 or feno¢brate 46 will similarly be interpreted by those equations as a loss in GFR rather than the changes in tubular secretion or creatinine production that they really are. Furthermore, published clinical studies of dopamine or dobutamine in heart failure have used creatininebased equations to demonstrate a bene¢cial e¡ect on renal function with a gain in GFR when it is really only interference with the Ja¡e reaction.…”
mentioning
confidence: 99%